Improvement of Feed Processing Skills using Probiotics in Glondok and Panggang Village Communities, Banyuwangi - Hamid, Iwan Sahrial (Jurnal Medik Veteriner, 2021)
This community empowerment aimed to introduce probiotics and improve breeders' skills in processing feed. Community empowerment activities that have been carried out include providing probiotics for ruminants which are given directly to breeders by visiting the location of the beef cattle pen. The community empowerment program was carried out for 5 months including counseling, training, evaluation, and training for cadres. From the evaluation results, there was an increase in affective from 20% to 60%, cognitive from 28% to 75%, and psychomotor from 8% to 80%. The cadres who were assigned will be assisted so that the development of livestock after being given probiotics can be monitored continuously.